Influence of Peripheral Substitution on the Magnetic Behavior of Single‐Ion Magnets Based on Homo‐ and Heteroleptic TbIII Bis(phthalocyaninate). Issue 4 (29th November 2012) - Ganivet, Carolina R.; Ballesteros, Beatriz; de la Torre, Gema; Clemente‐Juan, Juan M.; Coronado, Eugenio; Torres, Tomás
Abstract A series of homoleptic ([TbIII(Pc)2]) and heteroleptic ([TbIII(Pc)(Pc′)]) TbIII bis(phthalocyaninate) complexes that contain different peripheral substitution patterns (i.e., tert‐butyl or tert‐butylphenoxy groups) have been synthesized in their neutral radical forms and then reduced into their corresponding anionic forms as stable tetramethylammonium/tetrabutylammonium salts. All of these compounds were spectroscopically characterized and their magnetic susceptibility properties were investigated. As a general trend, the radical forms exhibited larger energy barriers for spin reversal than their corresponding reduced compounds. Remarkably, heteroleptic complexes that contain electron‐donor moieties on one of the two Pc ligands show higher effective barriers and blocking temperatures than their homoleptic derivatives. This result is assigned to the elongation of the NTb distances in the substituted macrocycle, which brings the terbium(III) ion closer to the unsubstituted Pc, thus enhancing the ligand‐field effect. In particular, heteroleptic [TbIII(Pc)(Pc′)] complex 4, which contains one octa(tert‐butylphenoxy)‐substituted Pc ring and one bare Pc ring, exhibits the highest effective barrier and blocking temperature for a single‐molecule magnet reported to date.